Key Concepts in Community Studies - Blackshaw, Tony; Blackshaw, Tony (SAGE Publications, 2009)
"This book is both insightful and engaging, enriched with diverse and up-to-date readings. Tony Blackshaw lays bare debates surrounding the uses and abuses of key concepts of community studies and breathes new life into community as theory and community studies as method." - Peter Bramham, Leeds Metropolitan University "I would highly recommend this book to any student who is studying communities and groups in society. The book and chapters are structured in a way that students will find it easy to move from one theme to another; to dip into relevant chapters when needed; to gain a good understanding of concepts and how and why they are applied to individuals and communities. The book encompasses both breadth and depth of key concepts and issues. This book will be compulsory reading on our Community Studies degree." - Lesley Groom, University of Bolton This book defines the current identity of community studies, provides a critical but reliable introduction to its key concepts and is an engaging guide to the key social research methods used by community researchers and practitioners. Concise but clear, it caters for the needs of those interested in community studies by offering cross-referenced, accessible overviews of the key theoretical issues that have the most influence on community studies today. It incorporates all of the important frames of reference including those which are: theoretical research focused practice and policy oriented political concerned about the place of community in everyday life. The extensive bibliographies and up-to-date guides to further reading reinforce the aim of the book to provide an invaluable learning resource. Interdisciplinary in approach and inventive in its range of applications this book will be of value to students studying sociology, social policy, politics and community development.